The Effect of Various Interventions on Patients Outcome In Peripheral Arterial Disease - Melissa, Philip; Chandrashekhar, Mahakalkar; Meenakshi, Yeola; Kshitija, Chandanwale (International Journal of Psychosocial Rehabilitation, 2020)
Background: Peripheral artery disease (PAD) is defined as impairment of the blood flowing to the extremities which is a result of atherosclerotic occlusive disease. The most classic symptom is pain over limbs on walking which resolves with rest (intermittent claudication) which occurs due to poor oxygenation of muscles of lower extremities. Objectives: Mainly to classify patients of PAD as per Fountain and Rutherford’s classification, Compare efficacy of various interventions based on treatment arms, Monitor response of treatment on claudication pain and claudication distance, Determine response of treatment on quality of life as assessed by SF-36 questionnaire and, Monitor short and long term effects of these interventions. Methodology: It is a prospective cohort study design studied for a duration of 2 years. Study Setting: Dept of Surgery, AVBRH, Sawangi(M), wardha. AMPLE SIZE: 75 (25 in each group). Groups: 1) PAD patients undergoing medical/ conservative management (N=25) 2) PAD patients treated or managed with intervention radiology (N=25). 3) PAD patients treated with combination of any of the two modalities like, IR and surgical (debridement/amputation) OR, Medical management followed by IR OR, Medical management followed by surgical management (debridement/amputation) (N = 25). Expected Results: All patients admitted with diagnosis of PAD will undergo comparison between medical, interventional radiological and surgical management which claims to improve the quality of living of patients with peripheral arterial disease. This study is basically inclined to prove that surgical management is the better form of management for improving quality of living of patient with PAD. Conclusion: Peripheral arterial disease is defined as a progressive disease with significant morbidity and mortality rate. The prevalence of this disease in general population is about 10–14%, affecting up to approximately 25% of those over 70 years; 65%–85% of affected individuals are asymptomatic with only a minority of population requiring revascularization or amputation. Keywords: Peripheral arterial disease, claudication pain, ankle brachial index, peripheral vascular disease, intermittent claudication, rest pain, thrombosis of arteries, gangrene.